Shari’ah supervisory board characteristics effects on Islamic banks’ performance: evidence from Malaysia - Nomran, Naji Mansour; Haron, Razali; Hassan, Rusni (Emerald Publishing Limited, 2018)
Islamic banks (IBs) must stay Shari’ah compliant to enhance their customer loyalty and obtain a competitive edge. Given the performance of Shari’ah supervisory board (SSB) continues to be a matter of concern especially for IBs across countries that have different regulatory environment, this paper aims to examine the effects of SSB characteristics on IBs’ performance in Malaysia being a country that applies the most extreme intervention of regulatory agencies (pro-active model).